2021
DOI: 10.1111/hae.14401
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for gene therapy in haemophilia: Results from the PAVING threshold technique survey

Abstract: Objectives:The aim of the Patient preferences to Assess Value IN Gene therapies (PAVING) study was to investigate trade-offs that adult Belgian people with haemophilia (PWH) A and B are willing to make when choosing between prophylactic factor replacement therapy (PFRT) and gene therapy. Methods:The threshold technique was used to quantify the minimum acceptable benefit (MAB) of a switch from PFRT to gene therapy in terms of 'Annual bleeding rate' (ABR), 'Chance to stop prophylaxis' (STOP), and 'Quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In studies including attribute ranking, 30,31,33 discrete choice experiments, 32 and trade-offs, 34 the top attributes for decisionmaking include annual bleeding rate, factor level expression, the uncertainty of long-term effects, impact on daily life, chance to stop prophylaxis, dose frequency and durability, impact on ability to participate in physical activity, frequency of monitoring, uncertainty regarding short-term or long-term significant safety issues and duration of follow-up on side effects. A key theme in those studies and the current survey is the unpredictability of the duration of therapeutic response and variability in factor expression.…”
Section: Discussionmentioning
confidence: 99%
“…In studies including attribute ranking, 30,31,33 discrete choice experiments, 32 and trade-offs, 34 the top attributes for decisionmaking include annual bleeding rate, factor level expression, the uncertainty of long-term effects, impact on daily life, chance to stop prophylaxis, dose frequency and durability, impact on ability to participate in physical activity, frequency of monitoring, uncertainty regarding short-term or long-term significant safety issues and duration of follow-up on side effects. A key theme in those studies and the current survey is the unpredictability of the duration of therapeutic response and variability in factor expression.…”
Section: Discussionmentioning
confidence: 99%
“…The review also identified 3 literature reviews [39][40][41] assessing patient preferences in haemophilia, all of which were not full journal articles. There have been two published studies exploring haemophilia patient preferences in relation to gene therapy: one DCE [37] and one utilising a threshold technique [42] . Surveyed audiences included physicians, patients, pharmacists, healthcare professionals and caregivers (either alone or in combination).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, a number of gene therapies are being developed for both haemophilia A and B. Two published studies to date have explored haemophilia patient preferences in relation to gene therapy: one DCE [37] and one utilising a threshold technique [42] . Whilst DCEs have been explored extensively in this paper, the threshold technique is a method that determines the maximal change in one attribute respondents are willing to accept to achieve a given change in another attribute [43] .…”
Section: Head-to-head Comparison Of Gene Therapy Studiesmentioning
confidence: 99%
“…Non-attendance to the information is evidenced in the short amount of time that respondents spent on the education material regardless of the format (2.36–3.84 minutes, while the video took over 9 minutes to view entirely, and reading the text-based information was expected to take 11 minutes). The long duration of the educational material may have led to non-attendance, but previous research with educational materials of comparable length has found that patients engage with the educational material when the treatment context was novel to the respondents [ 31 , 74 ]. The non-attendance in our study could be related to the high levels of disease experience that the sample had.…”
Section: Discussionmentioning
confidence: 99%